Low response rate to ATG‐based immunosuppressive therapy in very severe aplastic anaemia — A Swedish nationwide cohort study. (10th April 2018) - Vaht, Krista; Göransson, Magnus; Carlson, Kristina; Isaksson, Cecilia; Lenhoff, Stig; Sandstedt, Anna; Uggla, Bertil; Winiarski, Jacek; Ljungman, Per; Brune, Mats; Andersson, Per‐Ola
Abstract: Objectives: Antithymocyte globulin (ATG)‐based immunosuppression remains a cornerstone in aplastic anaemia (AA) treatment. However, most ATG studies are not population‐based and knowledge about real‐world results concerning response and outcome could offer important information for treating physicians. Methods: We have recently performed a nationwide retrospective cohort study on all AA patients diagnosed in Sweden in 2000–2011 and now present treatment and outcome data on patients receiving first‐line ATG. In total, 158 patients showed a 47.0% response rate which was similar in all age groups (range 41.5%‐51.7%) with no difference regarding ATG formulation. The response was significantly associated with severity grade—especially at time of treatment initiation: very severe (VSAA) 22.7%; severe (SAA) 54.5% ( P  <   .001); and non‐severe 88.5% ( P  <   .001). A logistic regression‐based predictive model indicated that VSAA patients with an absolute reticulocyte count <25 × 10 9 /L had only a 19% probability of response. In a multivariable analysis, age and VSAA at the time of treatment were the independent factors for inferior survival. Conclusions: Real‐world VSAA patients respond poorly to ATG which indicates the need for a different treatment approach. Our findings suggest that age alone should not be a discriminating factor for administering ATG treatment.